Methodology for developing curriculum for the graduate programs in the digital environment - Elena V. Buntova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to one of the priorities of higher educational institutions, which is the Institute of magistracy. The purpose of the article is to consider the specifics of the methodology of creating a master's course in the conditions of digital economy formation in the Russian Federation. Adaptation of master's programs to professional activity enables the sphere of science and education to respond quickly to the needs of industry and economy, in addition, the Institute of master's degree determines the possibilities of higher education institution in the field of training of highly qualified specialists in interdisciplinary fields. The basis of the presented research concerning the technology of creating a master's program training course in the digital economy are the theory of knowledge and activity, the theory of social and social conditionality of education, modern didactic theories and learning technologies, the methodology of teaching and learning activities, the methodology of developing a training course using electronic and computer technologies. The criteria of the content of the training course of the master's program are defined. The forms of the transmitted knowledge are offered and their application in the conditions of digitalization in education is proved. From the point of view of the aspect of Informatization and transparency in the control system of assimilation of transmitted knowledge in the magistracy justified such forms of control as the system of testing and implementation of undergraduates research work. One of the mandatory conditions for the creation of a master's degree course is the use of digital simulators, not tied to one workplace and unlimited information resources in order to ensure the possibility of training at any time convenient for the student and, in order to create conditions for continuous individual designed education.